Pemanfaatan Kartun Spongebob Berbahasa Arab dalam Meningkatkan Maharah Kalam Mahasiswa - Sulfikar; Takdir; Sardiyanah (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2022)
The Use of Arabic Spongebob Cartoons in Increasing the Maharah Kalam of PBA IAIM Sinjai Students. Thesis Sinjai: Arabic Language Education Study Program (PBA), Faculty of Tarbiyah and Teacher Training, IAI Muhammadiyah Sinjai, 2022. This study aims to prove the benefits of Spongebob cartoon media in Arabic in increasing the maharah kalam of PBA IAIM Sinjai students. This research uses an experimental research type through a quantitative approach. The objects in this study were 24 students of the Arabic Language Education Study Program class of 2020. The sampling technique used was the saturated sample technique. the increase in maharah kalam for the 2020 PBA IAIM Sinjai students after the application of the Arabic-language spongebob cartoon. This is evidenced by the average value of the student pre-test score of 65.46 while the post-test value of 82.08 and the gain value of 0.5 which indicates the increase in student's maharah kalam is at a moderate level. Based on the results of the hypothesis test (paired sample T-test) obtained a significance value of 0.000 <0.05 indicating a significant increase after treatment on the research variables, then H0 is rejected and Ha is accepted.